Development of MS ISO 9001:2008 management system for automotive excellence center - Nurul Jannah, Firdaus Ahmad Kamil (2011)
The purpose of this thesis is to study the development of Quality Management System at Automotive Excellence Center due to the MS ISO 9001:2008 requirement. The objective of this thesis are: 1) to study and enhance the knowledge on implementation of MS ISO 9001:2008 in industry, 2) to analyses the requirement for implementation of a quality management system at the Automotive Excellence Center of Faculty of Mechanical Engineering and 3) to develop a quality manual and quality procedure based on the requirement of MS ISO 9001:2008. ISO is the International Organization of Standardization in which it is the world wide federation of national standard bodies (ISO member bodies). It promotes the adaption of the process approach when developing, implementing and improving the effectiveness of a quality management system. ISO 9001:2008 is the continuation of MS ISO 9001:2000 with some changes made in the clauses. There are eight section modeled on the sectional organization of the ISO 9001:2008 standard. Section are further divided into several subsections representing main quality system processes. Each subsection defines general policies and basic principles for the pertinent quality system process, summarizes responsibilities and methods and references relevant operational procedures and other documents. The purpose of the development of quality manual is to define and describe the quality system as well as to define the authorities and responsibilities of the management personnel involved in the operation of the system. Furthermore, it is to provide a general description of all processes comprising the quality system. Another purpose of the development of the quality manual is to present the quality system to customers, suppliers, regulators and other external interested parties, and to inform them what specific controls are implemented at Automotive Excellence Center to assure quality.